A new species in the grassland leafhopper genus Stirellus Osborn & Ball (Hemiptera: Cicadellidae: Deltocephalinae: Stenometopiini) from Pakistan - Shah, Bismillah; Khan, Waqar; Naveed, Hassan; Shakeel, Muhammad; Duan, Yani (Zootaxa, 2022)
A new leafhopper species Stirellus pakistanicus Shah & Duan sp. n. is described from Attock region of the Punjab province of Pakistan. Habitus photos and illustrations of male genitalia of the new species are provided. An updated checklist and a distribution map of the known species of Stirellus from Pakistan are also given.